High baseline neutrophil-to-lymphocyte ratio predicts worse outcome in patients with metastatic BRAF-positive melanoma treated with BRAF and MEK inhibitors. Issue 5 (October 2018) - Teterycz, Paweł; Jagodzińska-Mucha, Paulina; Cybulska-Stopa, Bożena; Mariuk-Jarema, Anna; Kozak, Katarzyna; Koseła-Paterczyk, Hanna; Czarnecka, Anna M.; Rajczykowski, Marcin; Dziura, Robert; Galus, Łukasz; Mackiewicz, Jacek; Świtaj, Tomasz; et al.
Abstract : Neutrophil-to-lymphocyte ratio (NLR) has been shown to be prognostic in several solid malignancies. There are limited data regarding its value during novel therapies in patients with melanoma. The aim of the study was to assess the practical utility of this ratio in patients with BRAF -mutant melanoma treated with a combination of BRAF and MEK inhibitors (BRAFi/MEKi). We included 215 patients with inoperable or metastatic melanoma who underwent BRAFi/MEKi treatment between October 2015 and June 2017. Baseline NLR and other complete blood count-derived inflammatory markers were tested for association with overall survival and progression-free survival in univariate and multivariate models. On-treatment NLR was also assessed for relationship with these outcomes using the time-dependent Cox's proportional hazard model. Prognostic model based on NLR and lactate dehydrogenase (LDH) levels was also developed. Patients with NLR values more than four had poorer progression-free survival ( P <0.001, 1-year rates 51.6 vs. 26.7%) and overall survival ( P <0.001, 1-year rates 77.3 vs. 53.1%). In a multivariate model adjusted for LDH levels, metastatic sites and age baseline NLR ratio and delay in starting MEKi were deemed statistically significant (hazard ratio: 1.81; 95% confidence interval: 1.16–2.85; P =0.009 and hazard ratio: 2.06; 95% confidence interval: 1.24–3.44, P =0.005 respectively). In a model based on NLR and LDH, 1-year survival rates were 57, 40 and 23%, respectively if zero, one or both factors were elevated. Our results demonstrate the usefulness of NLR and a predictive model based on combinations of NLR and LDH as a prognostic markers during BRAFi/MEKi treatment. Our real-world data confirm the efficacy of BRAFi/MEKi therapy showed in the clinical trials.